Transient electromagnetic detection and numerical simulation analysis of the deformation characteristics of an old goaf in an alpine coal mine area - Wei, Zhan-Xi; Dong, Jian-Hui; Zhao, Meng; Xie, Fei-Hong; Li, Ying-Jun; Feng, Lin (Frontiers in Earth Science, 2023)
Abstract：The mining area in the alpine region will lead to the destruction of the ov erlying strata due to excessive mining, which will lead to a series of geological disast ers such as surface subsidence. Therefore, to accurately predict the deformation charac teristics of the overlying strata in the alpine mining area, taking the alpine mining are a in Qinghai Province of China as the research object, the location of the old goaf i n the coal mine is obtained by transient electromagnetic detection, and the results are used for numerical simulation. The numerical simulation results showed that after co al seam mining, the stress gradually increased from the surface to the bottom, and str ess concentration occurred at both ends and middle of the mining area. The displace ment change area was highly coincident with the stress concentration area, and the di splacement monitoring diagram was consistent with the horizontal displacement cloud analysis, showing a ' U ' type distribution. The research results provided a certain ref erence value for the study of surface mining subsidence in inclined coal seams in the future.